Neuroimmune and Mu-Opioid Receptor Alterations in the Mesocorticolimbic System in a Sex-Dependent Inflammatory Pain-Induced Alcohol Relapse-Like Rat Model - Cuitavi, Javier; Lorente, Jesús David; Campos-Jurado, Yolanda; Polache, Ana; Hipólito, Lucía (Frontiers in Immunology, 2021)
Evidence concerning the role of alcohol-induced neuroinflammation in alcohol intake and relapse has increased in the last few years. It is also proven that Mu-Opioid Receptors (MORs) mediate the reinforcing properties of alcohol and, interestingly, previous research suggests that neuroinflammation and MORs could be related. Our objective is to study neuroinflammatory states and microglial activation, together with adaptations on MORs expression in the mesocorticolimbic system (MCLS) during abstinence and relapse phases. To do so, we have used a sex-dependent rat model of complete Freund’s Adjuvant (CFA)-induced alcohol deprivation effect (ADE). Firstly, our results confirm that only CFA-treated female rats, the only experimental group that showed relapse-like behavior, exhibited specific alterations in the expression of phosphorylated NFκB, iNOS and COX2 in the PFC and VTA. More interestingly, the analysis of the IBA1 expression revealed a decrease of the microglial activation in PFC during abstinence and an increase of its expression in the relapse phase, together with an augmentation of this activation in the NAc in both phases that only occur in female CFA-treated rats. Additionally, the expression of IL1β also evidenced these dynamic changes through these two phases following similar expression patterns in both areas. Furthermore, the expression of the cytokine IL10 showed a different profile than that of IL1β, indicating anti-inflammatory processes occurring only during abstinence in the PFC of CFA-female rats but not during the re-introduction phase in PFC nor in the NAc. This data indicates a downregulation of microglial activation and pro-inflammatory processes during abstinence in the PFC, whereas an upregulation can be observed in the NAc during abstinence that is maintained during the re-introduction phase only in CFA-female rats. Secondly, our data reveals a correlation between the alterations observed in IL1β, IBA1 levels and MOR levels in the PFC and NAc of CFA-treated female rats. Although premature, our data suggests that neuroinflammatory processes, together with neural adaptations involving MOR, might play an important role in alcohol relapse in female rats, so further investigations are warranted.